The Psalmic Oral Formula Revisited: A Cognitive-Performative Approach - Coleman, Stephen M. (Biblical interpretation, 2019)
In the wake of Milman Parry's and Alfred Lord's groundbreaking discovery of oral composition in Homeric epics, biblical scholars analyzed the formulaic language of the biblical Psalms with a view toward establishing a similar compositional function. This approach met with little success. Among the many recent refinements to the Oral-Formulaic theory is the distinction between oral composition and oral conception, a distinction which allows for identifying oral features of a "text" which do not necessarily reflect composition in performance. The goal of this article is two-fold. First this article proposes a new model for identifying oral formulas based on the theory of prototypical categorization developed within the field of cognitive sciences, particularly cognitive linguistics. Second, this article argues that the psalmic oral formulas are best understood as linguistic registers which evoke a performance arena, a feature of orally derived literature described most extensively by John Miles Foley.